Implementation of Method and Partnership Managerial Operation System in Environmentally Friendly Rice Cultivation - Sukarsono`, Agustin; Daroini, Ahsin; Wahyu HD, Bambang (Universitas KH. A. Wahab Hasbullah, 2017)
The need for a progressive organization is based on the quality and integrity of the human resource as one of its fundamental elements. So that an organization must have a management function within the organization, while the management functions of the four is planning (planning), organizing (organizing), actuating (briefing), controlling (supervision). It is intended that an organization can be run in accordance with the objectives to be achieved by an organization. In this study, the source of the data used is organic rice farming model with planting patterns healthy and mandate (PTSA), which has been applied by the working group (gapoktan) LM3 POMOSDA. While the method of problem-solving by using effective methods of problem-solving to find simultaneously solve the problems of guidance and assistance to farmer group in POMOSDA ( Pondok Modern Sumber Daya At-Taqwa). The expected outcome of this research is to determine consumer loyalty and the partners of farmers while recognizing the success of organizational development at the farm agribusiness independent organization rooted in society Pondok Modern Sumber Daya At-Taqwa (LM3 POMOSDA) Nganjuk Regency